2016
DOI: 10.1038/srep37745
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of genotypic adaptation to the exposure to volcanic risk at the dopamine receptor DRD4 locus

Abstract: Humans have colonized and adapted to extremely diverse environments, and the genetic basis of some such adaptations, for example to high altitude, is understood. In some cases, local or regional variation in selection pressure could also cause behavioural adaptations. Numerous genes influence behaviour, such as alleles at the dopamine receptor locus D4 (DRD4), which are associated with attitude toward risk in experimental settings. We demonstrate genetic differentiation for this gene, but not for five unlinked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
4
2
Order By: Relevance
“…In this paper, we found that the 7R allele of DRD4 affects risk-attitudes by an additivity effect, not a dominance effect. This is in contrast with previous research 37 who found that heterozygotes 2R/4R had lower risk tolerance. It is unclear if this difference comes from the type of risky environment considered (background volcanic risk or risky subsidence type), or comes from the different alleles involved (2R and 4R in Indonesia, or 7R in Senegal).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this paper, we found that the 7R allele of DRD4 affects risk-attitudes by an additivity effect, not a dominance effect. This is in contrast with previous research 37 who found that heterozygotes 2R/4R had lower risk tolerance. It is unclear if this difference comes from the type of risky environment considered (background volcanic risk or risky subsidence type), or comes from the different alleles involved (2R and 4R in Indonesia, or 7R in Senegal).…”
Section: Discussioncontrasting
confidence: 99%
“…However, we did not find evidence of genetic differentiation at the DRD4 locus relative to 29 unlinked microsatellites loci (Table S.8 and Figure S.2). Moreover, if there was genetic differentiation, it would move in the opposite direction as the risk-vulnerability hypothesis found in previous work for DRD4 37 , as the 7R allele, favoring more risk-tolerant attitudes, is more prevalent in the risky area. Altogether, our results indicate that no selection at the DRD4 locus is apparent in our sample.…”
Section: Figurementioning
confidence: 79%
“…In this paper, we find that the 7R allele of DRD4 affects risk-attitudes by an additivity effect, not a dominance effect. This is in contrast with previous research 35 who found that heterozygotes 2R/4R had lower risk tolerance. It is unclear if this difference comes from the type of risky environment considered (background volcanic risk or risky subsidence type), or comes from the Note: A higher level of risk-tolerance indicates the choice of a riskier lottery by participants in the lottery choice task.…”
Section: Discussioncontrasting
confidence: 99%
“…While the sample would satisfy conditions for a genetic adaptation to habitat 37 (limited migration with 74% of grandparents of participants of the risky area born in the same village, Table S.3, and a strong economic benefit to living in the area), we find no specific genetic differentiation at DRD4 locus relative to 29 unlinked microsatellites loci (Table S.4 and Figure S.2). Moreover, if there was genetic differentiation, it would move in the opposite direction as the risk-vulnerability hypothesis found in previous work for DRD4 35 , as the 7R allele, favoring more risk-tolerant attitudes, is more prevalent in the risky area. Altogether, our results indicate that no selection at the DRD4 locus is apparent in our sample.…”
Section: /8mentioning
confidence: 79%
See 1 more Smart Citation